Extent and Determinants of Resource Misallocation: A Cross-section Study for Developing Countries - Fossati, Román (2018)
Several factors distorting the allocation of resources across heterogeneous production units can be responsible for differences in total factor productivity (TFP) and output per capita across countries. Identifying and measuring the effect of specific distortions at country level have relevant policy implications. This paper investigates the sources of resource misallocation in developing countries. The main contribution of it is to study the role of particular idiosyncratic distortions not considered in the current literature using comparable methodology and data for a broad set of developing countries. The results indicate that, in contrast with previous evidence documented in the literature, distortions affecting international trade and related to business licensing and operation permits as well as to informality are key factors damaging TFP in the set of developing countries we considered.